RANCANG BANGUN MONITORING SPAREPART MENGGUNAKAN METODE AGILE BERBASIS WEBSITE PADA CV. MULYA JAYA DIESEL - Heppy Azizzul Khakim; Achmad Nur Hidayat; Roeslan Djutalov (Journal of Research and Publication Innovation, 2023)
The forklift spare parts industry is increasingly complex and dynamic, requiring an effective monitoring system to optimize inventory management and minimize shortages. This research aims to design and implement a website-based spare parts monitoring system with an agile approach at CV. Mulya Jaya Diesel. The Agile method was chosen for its ability to provide solutions that adapt and respond to rapidly changing business needs. This research will focus on analyzing user needs and iterative development processes to more quickly adjust to changing needs. The proposed system will provide real-time information regarding inventory availability. This way, companies can make more timely decisions when planning purchases and reduce the risk of inventory shortages. The implementation of the website as the main platform allows easy and quick access from various devices, enhances collaboration between teams, and facilitates effective communication. It is expected that the results of this study can improve the operational efficiency of CV. Mulya Jaya Diesel in spare parts management, as well as contribute to further understanding of the application of Agile methods in the context of the spare parts distribution industry